2020
DOI: 10.1002/trc2.12109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activities on dementia‐related biomarkers: A systematic review of randomized controlled trials

Abstract: Introduction Physical activities (PA) may lead to improved cognition in mild cognitive impairment (MCI), Alzheimer's disease (AD), and dementia. The mechanisms mediating potential PA effects are unknown. Assessment of PA effects on relevant biomarkers may provide insights into mechanisms underlying potential PA effects on cognition. Methods We systematically reviewed randomized controlled trials (RCTs) that studied PA effects on biomarkers in MCI, AD, and dementia populations. We examined whether biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…These mechanisms could have contributed to the null associations for ST and MSBD in the present study. Few studies have examined the associations of PA and SB with early AD pathologic markers such as amyloid‐beta species and tau protein, and findings are equivocal 56 . Additional research is warranted to better understand how PA and SB influence the heterogenous mechanisms involved in the pathogenesis of MCI, dementia, and dementia subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…These mechanisms could have contributed to the null associations for ST and MSBD in the present study. Few studies have examined the associations of PA and SB with early AD pathologic markers such as amyloid‐beta species and tau protein, and findings are equivocal 56 . Additional research is warranted to better understand how PA and SB influence the heterogenous mechanisms involved in the pathogenesis of MCI, dementia, and dementia subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with study of Coelho-Júnior et al, who also observed cognitive function improvements without any positive changes in BDNF, 44 while other studies showed BDNF improvements in conjunction with improvements in physical fitness and cognitive function. 2 , 16 One possible rationale for these contradictory findings is the baseline cognitive characteristics of the subjects. For example, a previous study noted that increases of BDNF in response to an exercise program occurred in individuals with mild cognitive impairment, 15 whereas the subjects in our study did not have any cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
“…13 Although many factors likely contribute to the positive effects of exercise on cognitive function, two of the most important factors include increased blood flow to the brain (providing the necessary nutrients 14 and increased neurotrophic factors in response to physical activity (especially brain-derived neurotrophic factor (BDNF))). 1,15,16 BDNF is a polypeptide growth factor that is expressed in the central nervous system and is considered to be extremely important for learning and forming memories. It plays a crucial role in regulating synaptic plasticity, and it also plays a role in neurogenesis and neuronal survival.…”
Section: Introductionmentioning
confidence: 99%
“…Fifth, exploratory analyses on changes in speech characteristics could yield promising behavioral markers of early cognitive decline, responding to the urgent need to identify ecologically valid outcomes sensitive to trials effects in the dementia research field ( 3 ). Finally, while exercise-based interventions often aim to examine the underlying biological mechanisms of efficacy ( 57 ), how and why social interaction affects cognition is yet to be discovered. We will use baseline characteristics of brain structures and connectivity to investigate who gains most in addition to the intervention efficacy (pre-post changes).…”
Section: Discussionmentioning
confidence: 99%